A survey of substance use for cognitive enhancement by university students in the Netherlands - Schelle, Kimberly J.; Olthof, Bas M. J.; Reintjes, Wesley; Bundt, Carsten; Gusman-Vermeer, Joyce; van Mil, Anke C. C. M. (Frontiers in Systems Neuroscience, 2015)
Background: Pharmacological cognitive enhancement, using chemicals to change cellular processes in the brain in order to enhance one’s cognitive capacities, is an often discussed phenomenon. The prevalence among Dutch university students is unknown. Methods: The study set out to achieve the following goals: (1) give an overview of different methods in order to assess the prevalence of use of prescription, illicit and lifestyle drugs for cognitive enhancement (2) investigate whether polydrug use and stress have a relationship with cognitive enhancement substance use (3) assessing opinions about cognitive enhancement prescription drug use. A nationwide survey was conducted among 1572 student respondents of all government supported Dutch universities. Results: The most detailed level of analysis ─ use of specific substances without a prescription and with the intention of cognitive enhancement ─ shows that prescription drugs, illicit drugs and lifestyle drugs are respectively used by 1.7%, 1.3% and 45.6% of the sample. The use of prescription drugs and illicit drugs is low compared to other countries. We have found evidence of polydrug use in relation to cognitive enhancement. A relation between stress and the use of lifestyle drugs for cognitive enhancement was observed. We report the findings of several operationalizations of cognitive enhancement drug use to enable comparison with a wider variety of previous and upcoming research. Conclusions: Results of this first study among university students in the Netherlands revealed a low prevalence of cognitive enhancement drug use compared to other countries. Multiple explanations, such as a difference in awareness of pharmacological cognitive enhancement among students, accessibility of drugs in the student population and inclusion criteria of enhancement substances are discussed. We urge enhancement researchers to take the different operationalizations and their effects on the prevalence numbers into account.